2020
DOI: 10.1111/ajgw.12459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of remediation strategies for decreasing ‘reductive’ characters in Shiraz wines

Abstract: Background and Aims: Winemakers utilise various remediation strategies for decreasing 'reductive' characters in wine. Remediation strategies, such as the addition of diammonium phosphate (DAP) during fermentation, copper fining, the addition of fresh lees or lees products to wine, and aeration of the must during and after fermentation, are commonly employed in an effort to prevent the formation or to remove undesirable volatile sulfur compounds. In this study, the relative effectiveness of five strategies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 61 publications
4
16
0
Order By: Relevance
“…In Trial 1, however, H 2 S concentration in Control wines (T1_NT) was high [11 μg/L (Table S2)] and aeration during fermentation resulted in a substantial decrease in its concentration to a level comparable to the other three trials. This suppression of H 2 S observed in Trial 1 is consistent with previous observations (Bekker et al 2016, 2021). Overall, the data presented in this work suggest that when H 2 S concentration is already low, aeration has limited capacity to further decrease it.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In Trial 1, however, H 2 S concentration in Control wines (T1_NT) was high [11 μg/L (Table S2)] and aeration during fermentation resulted in a substantial decrease in its concentration to a level comparable to the other three trials. This suppression of H 2 S observed in Trial 1 is consistent with previous observations (Bekker et al 2016, 2021). Overall, the data presented in this work suggest that when H 2 S concentration is already low, aeration has limited capacity to further decrease it.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, aeration has been shown to increase metabolic flux through acyl‐CoA (Saerens et al 2006), a metabolite pool that may limit ester synthesis (Jouhten et al 2008) and might further contribute to the observed increases in short branched‐chain ethyl esters. Overall, our observations are broadly consistent with the existing reports that describe the impact of aeration on yeast‐derived volatile aroma compounds in red wine (Bekker et al 2016, 2021, Picariello et al 2020).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations